2006
DOI: 10.1038/sj.bjc.6603122
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and breast cancer risk

Abstract: Many, but not all studies of birth weight and subsequent breast cancer risk suggest a positive association, with the most consistent finding being an association in younger or premenopausal women, often with either no or a reduced association among postmenopausal women (Ekbom et al, 1992;Michels et al, 1996;Sanderson et al, 1996;De Stavola et al, 2000;Innes et al, 2000;Andersson et al, 2001;Hilakivi-Clarke et al, 2001;Titus-Ernstoff et al, 2002;Vatten et al, 2002Vatten et al, , 2005Ahlgren et al, 2003;Kaijser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Two studies did not provide adequate information for either dichotomous comparisons or trend analysis, 21,30 2 twins studies were excluded because we were concerned with differences between twins and general birth populations, particularly with regard to birth weight, 31,32 and 10 other studies were excluded because their results were included in other detailed publications that provided more comprehensive results or adequate information. 10,16,17,19,20,22,[33][34][35][36] Thus, the present meta-analysis includes 18 unique studies: 11 case-control studies, 9,13,18,23,[37][38][39][40][41][42][43] and 7 cohort studies 11,12,14,15,24,44,45 (Tables 1 and 2).…”
Section: Study Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies did not provide adequate information for either dichotomous comparisons or trend analysis, 21,30 2 twins studies were excluded because we were concerned with differences between twins and general birth populations, particularly with regard to birth weight, 31,32 and 10 other studies were excluded because their results were included in other detailed publications that provided more comprehensive results or adequate information. 10,16,17,19,20,22,[33][34][35][36] Thus, the present meta-analysis includes 18 unique studies: 11 case-control studies, 9,13,18,23,[37][38][39][40][41][42][43] and 7 cohort studies 11,12,14,15,24,44,45 (Tables 1 and 2).…”
Section: Study Identificationmentioning
confidence: 99%
“…The study populations included participants from the United States, 9,11,[39][40][41]43,44 Europe, 12,15,23,24,37,38,42,45 and China, 18 for a total of 16,424 women with breast cancer. The cases in these studies were primarily obtained from cancer registries, hospital records, or both.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Birth-weight has been reported to be positively associated with breast cancer [6][7][8][9][10], particularly among premenopausal women [6,10]. However, the limited research so far into the association between birth weight and mammographic density has reported inconsistent findings [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, several studies have observed that perinatal factors, including birth weight, may influence later susceptibility of chronic diseases including breast cancer (25), (26), (5), (27), (28). Moreover, the association related to breast cancer has been complicated by contradictory results (29), (30) because some have observed a protective effect of low birth weight (25), whereas others have not (31). We have previously hypothesized that birth size may influence later responsiveness of ovarian function and have shown that, among adult women ovarian response to physical activity depends on their size at birth (32).…”
mentioning
confidence: 99%